Comparative Postoperative Outcomes After Rotator Cuff Repair in Tobacco and Nontobacco Nicotine Users - M. Lane Moore; Alejandro M. Holle; William H. Rankin; Collin L. Braithwaite; Eugenia Lin; Joseph C. Brinkman; Jeffrey D. Hassebrock (Orthopaedic Journal of Sports Medicine, 2026)
Background: Tobacco use is a known risk factor for poor healing after rotator cuff repair (RCR), but the effects of nontobacco nicotine products remain unclear. Purpose: To compare postoperative complications among nontobacco nicotine users, tobacco users, and nonusers undergoing RCR. Study Design: Cohort study; Level of evidence, 3. Methods: Using the PearlDiver database, the authors identified patients who underwent arthroscopic RCR with ≥2 years of follow-up. Three 1:1 propensity-matched comparisons were conducted: nontobacco nicotine users versus nonusers (n = 4844), tobacco users versus nonusers (n = 19,182), and nontobacco nicotine users vs tobacco users (n = 4882). Outcomes included 90-day complications and 2-year revision surgeries. Results: Nontobacco nicotine users had mildly higher rates of lysis of adhesions than controls (0.7% vs 0.4%; OR, 1.95; P = .033) but no other significant differences. Tobacco users showed increased rates of acute kidney injury (AKI), pneumonia, infections, emergency department (ED) visits, readmissions, and revision surgery compared to controls. Compared to tobacco users, nontobacco nicotine users had moderately strong lower risks of pneumonia (0.6% vs 1.2%; OR, 0.46), ED visits (8.8% vs 13.6%; OR, 0.62), and readmissions (0.8% vs 1.5%; OR, 0.54) (all P < .01). Conclusion: While nontobacco nicotine use was associated with a modestly increased risk of lysis of adhesions after RCR, it did not significantly elevate the risk of major medical complications, infections, or revision surgery when compared to nonnicotine users. In contrast, tobacco users demonstrated consistently worse postoperative outcomes across multiple domains, including higher rates of AKI, pneumonia, surgical site infection, ED visits, readmissions, and revision procedures. Notably, when compared directly to tobacco users, nontobacco nicotine users had significantly lower rates of pneumonia, ED utilization, and readmissions. These findings suggest that although nontobacco nicotine products may not be entirely benign, their perioperative risk profile appears to be less severe than that of traditional tobacco use.